Upgrading of bio-oil into advanced biofuels and chemicals. Part II. Importance of holdup of heavy species during the hydrotreatment of bio-oil in a continuous packed-bed catalytic reactor - Chaiwat, Weerawut; Gunawan, Richard; Gholizadeh, Mortaza; Li, Xiang; Lievens, Caroline; Hu, Xun; Wang, Yi; Mourant, Daniel; Rossiter, Angelina; Bromly, John; Li, Chun-Zhu (Elsevier Ltd, 2013)
This study has investigated the observed product distribution as a function of temperature and liquid hourly space velocity (LHSV) from the continuous hydrotreatment of pyrolysis bio-oil in a packed-bed catalytic reactor using a Pd/C catalyst. Our results show that, at a constant overall LHSV value, the time required to achieve a steady state formation rate varies widely among the various species in the raw bio-oil and hydrotreated product. Due to the complexity of bio-oil composition, LHSV is not an accurate parameter to evaluate the residence time of various species in a continuous catalytic reactor. The holdup of heavy species in the catalyst must have occupied some active sites while the heavy compounds were slowly hydrogenated. This caused the active sites to be unavailable for other reactions during the continuous hydrotreatment.